Penggunaan Media Pembelajaran Online pada Diklat Program Keluarga Harapan (PKH) di BBPPKS Regional 1 Sumatera - Elimendra, Romi; Sunarti, Vevi (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research was motivated by the high learning outcomes in training PKH Regional BBPPKS 1 Sumatra. This was evidenced by the learning outcomes of participants who are above average or reach the graduation target of 7.0 which is set by the BBPPKS institution. The researcher suspects that the cause of the learning outcomes of the participants was high because Widyaiswara and the participants were able to use online learning media well. This study aims to look at the use of online learning media in the Family Hope Training Program (PKH) at BBPPKS Regional 1 Sumatra. This type of research is quantitative descriptive research. The population in this study is the training participants PKH of 40 people. The sampling technique used was Cluster Random Sampling. Samples taken as much as 65% of the total population of 24 people. The technique of collecting data uses the questionnaire. While the data collection tool is a list of statements. The data analysis techniques using the percentage formula. The results showed that the use of online learning media in PKH training in BBPPKS Regional 1 Sumatra was (a) the use of online learning media from the aspect of material relevance that the material provided was relevant to the needs of participants (b) the use of online learning media from the aspect of Widyaiswara's ability that Widyaiswara able to provide material well (c) the use of online learning media from the aspect of ease of use for participants that participants are able to use learning media well (d) use of online learning media from the aspect of material availability that the material provided to participants is well provided (e) the use of online learning media from the aspect of program usefulness that the program implemented is beneficial for participants. This is evidenced by the majority of training participants always giving statements. Based on the results of the study it is recommended for institutions, managers and Widyaiswara to continue to improve and maintain the use of online learning media in PKH training in BBPPKS Regional 1 Sumatra.